The Influence of Cigarette Consumption Towards Poverty in Central Java Province - Agnes Marisca Dian Sari (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2016)
The aims of this research were to find out the effects of poverty on cigarette consumption in Central Java in 2013 and to recognize the effects of tax cigarette on cigarette consumption in Central Java in 2013. The type of the data used was secondary data. The analysis method used was the regression of Ordinary Least Square (OLS) with the cross section data of 2013 in 35 Districts of Central Java Province.The research results show that when the Poverty Line increases, it increases cigarette consumption. The variable on Poverty Line has effect on cigarette consumption in Central Java in 2013. The variable of cigarette tax has positive insignificant value. The variables of poverty and cigarette tax are able to explain the level of cigarette consumption of 0.1263%, and the remaining variables are explained by the other variables. F- statistic is 2,31, F-table is 1,37, and t-table is 2.034. Based on the research results, it can be concluded that there is a significant association between cigarette consumption and poverty in Central Java in 2013. When cigarette consumption rose, it increased the poverty in Central Java in 2013. The association between cigarette consumption and cigarette tax in Central Java in 2013 was not significant but had positive value. It means that the tax policy in Central Java is not able to reduce cigarette consumption in Central Java in 2013. Although there has been a cigarette tax, the cigarette consumption continues to increase.